THE IMPORTANCE OF MELATONIN IN SLEEP REGULATION AND GLYCEMIC CONTROL IN REPRODUCTIVE AGE PATIENTS WITH TYPE 2 DIABETES MELLITUS - Makhmudova Farangiz Batirovna; DSc. Narimova Gulchekhra Dzhumaniyazovna (Modern American Journals, 2025)
Melatonin, a pineal gland hormone, has traditionally been considered a key regulator of circadian rhythms, especially sleep. However, modern studies indicate its involvement in metabolic processes, including the regulation of carbohydrate metabolism. In patients with type 2 diabetes mellitus of reproductive age, impaired melatonin secretion is associated with worsening glycemic control, increased insulin resistance, and sleep disturbance. This review article examines current concepts of the role of melatonin in the regulation of sleep and glucose homeostasis, as well as the possibility of its use as an adjuvant therapy in patients with type 2 diabetes mellitus.
Keywords: Melatonin, circadian rhythms, type 2 diabetes mellitus, sleep, glycemic control, insulin resistance, reproductive age.